THE DISPUTE SETTLEMENT FOR CONSUMER PROTECTION BY THE CONSUMER DISPUTE SETTLEMENT AGENCY IN LEGAL ASSURANCE PERSPECTIVE - Jaenudin Umar; Endang Sutrisno; Abdullah Abdullah (UNISSULA, 2023)
The concept of consumer protection is to guarantee legal certainty to consumers, namely efforts to empower consumers to obtain or determine their choice of goods and/or services and to defend or defend their rights if business actors harm them. Legal norms to protect the interests of consumers are not sufficient. Therefore, to achieve a balance in protecting the interests of consumers and business actors, a clear legal order is needed so that a healthy economy can be realized. Consumer protection norms in the Consumer Protection Law System, as a fundamental norm, become the criteria for determining alleged violations of consumer rights. The aim of this study is to provide an alternative for resolving cases, a form of embodiment of the implementation of consumer rights protection policies. The approach method used in this research is juridical sociological. However, there are still legal loopholes that often occur. May harm the interests of consumers. The existence of regulations that still have to be synchronized and harmonized between the Consumer Protection Act and the rules governing Arbitration and Alternative Dispute Resolution issues because the Consumer Protection Law formulates rules for resolving consumer disputes by separate arbitration, which is relatively different from the basic concept of the arbitration mechanism which generally accepted so that the settlement of consumer disputes becomes legal uncertainty.